2023
DOI: 10.1001/jamanetworkopen.2023.7482
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Change in Body Size With All-Cause and Cause-Specific Mortality Among Healthy Older Adults

Abstract: ImportanceThe association between weight change and subsequent cause-specific mortality among older adults is not well described. The significance of changes in waist circumference (WC) has also not been compared with weight change for this purpose.ObjectiveTo examine the associations of changes in body weight and WC with all-cause and cause-specific mortality.Design, Setting, and ParticipantsThis cohort study is a post hoc analysis of data from the Aspirin in Reducing Events in the Elderly (ASPREE) randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…In this context of our study findings, the recent highlight on the need to monitor and investigate weight loss in older adults aged over 65 years by the ASPREE trial is informative [ 32 ]. This trial reported that a weight loss of 5% or more and reductions in waist circumference were associated with increased mortality [ 32 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this context of our study findings, the recent highlight on the need to monitor and investigate weight loss in older adults aged over 65 years by the ASPREE trial is informative [ 32 ]. This trial reported that a weight loss of 5% or more and reductions in waist circumference were associated with increased mortality [ 32 ].…”
Section: Discussionmentioning
confidence: 93%
“…In this context of our study findings, the recent highlight on the need to monitor and investigate weight loss in older adults aged over 65 years by the ASPREE trial is informative [ 32 ]. This trial reported that a weight loss of 5% or more and reductions in waist circumference were associated with increased mortality [ 32 ]. The authors of the ASPREE trial explained that weight loss commonly precedes a diagnosis of chronic diseases in older adults and that it is associated with a reduced appetite and food intake.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, the importance of recognizing and addressing frailty, sarcopenia, cachexia, and malnutrition in HF patients should also be acknowledged in order to improve their clinical outcomes. Particularly, identifying loss of weight over time may also be an important marker in this population as this has recently shown to be associated with increased all-cause and CVD specific mortality in a healthy elderly cohort ( 65 ). To achieve those goals, we recommend managing stable chronic HF patients in an outpatient heart failure program with the collaboration of a multidisciplinary team consisting of cardiologists, nutritionists, and geriatricians.…”
Section: Discussionmentioning
confidence: 99%
“…Weight gain (≥ 2.5-<10.0 kg) from early to middle adulthood may increase the risk of development of major chronic diseases (e.g., type 2 diabetes, cardiovascular disease, obesity-related cancers), and increased risk of morality among US adults compared with participants who maintained a stable weight [ 9 ]. Weight l loss of 5–10% of body weight in older adults was associated with an increase in all-cause mortality than those who had stable weight [ 10 12 ]. Additionally, significant weight gain or loss (> 10%) is associated with increased all-cause hospitalization compared to those with stable weight.…”
Section: Introductionmentioning
confidence: 99%